(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
New developments in the emerging field of Behavioral Economics have been made towards an updated account of what would be classically viewed as “irrational behavior”, yielding significant changes in classical economic models for studying decision-making. However, Michie et al. (2011) points out that an evidence-based behavior model with internal consistency has not been yet developed. In most applications, theories are rooted in common sense or intuitive knowledge assumptions on behavior. We argue that Behavioral Psychology offers a relevant body of evidence and theories that can help Economic Sciences and Behavioral Economics advance towards a robust, evidence-based comprehension of the nature of a behavior of interest. Such contributions can be used to better plan applications, as it also grants a better understanding of independent variables that are key to predict behavioral outcomes. Relevant paths through which Behavioral Psychology and Behavioral Economics can benefit from better establishing communication between areas will be discussed.